2019
DOI: 10.1530/joe-18-0541
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D deficiency and developmental origins of health and disease (DOHaD)

Abstract: Vitamin D is an essential nutrient that is metabolized in the body to generate an active metabolite (1,25(OH)2D) with hormone-like activity and highly diverse roles in cellular function. Vitamin D deficiency (VDD) is a prevalent but easily preventable nutritional disturbance. Emerging evidence demonstrates the importance of sufficient vitamin D concentrations during fetal life with deficiencies leading to long-term effects into adulthood. Here, we provide a detailed review and perspective of evidence for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 138 publications
(119 reference statements)
1
29
0
Order By: Relevance
“…Vitamin D (1α, 25-dihydroxyvitamin D3) is a steroid hormone traditionally associated with bone homeostasis; however, accumulating evidence suggests a wider biological role for the VD3 signaling axis in metabolic control. Low levels of VD3 during early development have been linked to obesity and metabolic disorders falling under the umbrella of dyslipidemia and adiposity 6 12 , 29 . To address the role of vitamin D in metabolic control we developed a dietary VDD model with greater capability of mimicking systemic human VDD than previously published genetic knockout models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vitamin D (1α, 25-dihydroxyvitamin D3) is a steroid hormone traditionally associated with bone homeostasis; however, accumulating evidence suggests a wider biological role for the VD3 signaling axis in metabolic control. Low levels of VD3 during early development have been linked to obesity and metabolic disorders falling under the umbrella of dyslipidemia and adiposity 6 12 , 29 . To address the role of vitamin D in metabolic control we developed a dietary VDD model with greater capability of mimicking systemic human VDD than previously published genetic knockout models.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies demonstrate a correlation between low maternal vitamin D levels during pregnancy and small gestational size followed by high BMI’s at one and three years of age 25 . These studies provide initial evidence for an inverse relationship between maternal vitamin D levels and adverse metabolic health outcomes in offspring including excess adiposity and insulin resistance; however, not all studies have demonstrated a definite relationship between VDD and cardiometabolic risk factors in offspring 6 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This study focuses on the liver metabolomic impact of maternal vitamin D deficiency (VDD), a global health concern with some populations having VDD rates >80% ( 25 ). Maternal VDD has major implications for fetal and maternal health ( 26 ). It is well known that VDD impairs human fetal growth and skeletal and extraskeletal health ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%